Anatase TiO2 films obtained by cathodic arc deposition - Kleiman, Ariel Javier (2007)
TiO2 thin films were prepared on glass substrates at different temperatures employing an unfiltered cathodic arc device. The temperature values were varied from room temperature to 400 ºC. The crystalline structure of the films was determined by X-ray diffraction. The surface morphology was studied by scanning electron microscopy and atomic force microscopy. Transmittance in UV-visible region was also measured. All films deposited at temperatures lower than 300 ºC were amorphous, whereas films obtained at higher temperatures grew in crystalline anatase phase. Phase transition amorphous-to-anatase was observed after post-annealing at 400 ºC. The average transmittance value for all films was higher than 80%, a comparison among the films obtained at different temperatures shown the transmittance value slightly higher for films obtained at highest temperatures. Grain size for as-deposited crystalline films was determined approximately in 20 nm, with a surface roughness of about 2 nm.